Application of chitin and chitosan as film formers in propranolol hydrochloride sustained-release film coated tablets compared with celluloses - Chirasak Kusonwiriyawong (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 1994